Efficacy of Intravitreal Anti Vascular Endothelial Growth Factor Injection Compared to Focal Therapy in Pediatric Patients with Coats Disease - Alia Nesa Utami; Julie Dewi Barliana (Majalah Oftalmologi Indonesia, 2022)
Introduction: Coats disease is a retinal vascular disorder that may lead to progressive exudative retinal detachment. The standard regiment of treatment is focal therapy. However, its effectiveness may decrease when more than two quadrants of the retina exhibit vascular abnormalities. Thus, recent studies tried to use anti vascular endothelial growth factor (anti-VEGF) as therapy for the vascular problems. Aims: Comparing the efficacy between anti-VEGF injection and standard therapy regiment such as focal laser therapy. Methods: Literature searching was conducted through PubMed, ScienceDirect, Google Scholar, ProQuest, and SpringerLink. Search terms included "Coats’ Disease" and mesh terms of “Anti- VEGF". The efficacy is assessed based on Best-Corrected Visual Acuity (BCVA) and improvement in fundus manifestations. Results: All of the studies that conducted primary intravitreal anti-VEGF treatment were followed by necessary ablative treatment. These studies, such as by Yang Q and Zheng XX, et al. showed remarkable improvements in both visual acuity and anatomical outcomes. Laser therapy also gained satisfactory result in upgrading clinical stages, even though some complications including subretinal fibrosis, cataract, and vitreous hemorrhage were reported. A comparative study by Ray R, et al. noted that group undergoing anti-VEGF might require longer treatment sessions despite possible benefits. Conclusion: Anti-VEGF agents can be used as neoadjuvant in standard therapy. It did not reduce the time for full treatment, but the resolution of disease was seen in the most severe cases treated with combination therapy.